Edukasi Personal Hygiene pada Remaja sebagai Upaya Pencegahan Penyakit Infeksi pada Siswa SMA di Kota Palangka Raya - Normila Normila; Harlyanti Muthma'innah Mashar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Diseases caused by negligence in maintaining personal hygiene are still a public health problem in Indonesia, one of which is school-age children. School-age children are an age group that is vulnerable to various health problems. The number of school-age children, from early childhood to adolescence, still often neglects personal hygiene. The result of poor personal hygiene can increase the risk of infection, which can lead to various diseases. For that, health-related behaviors must be applied to children as early as possible. This activity targets students at MAN Kota Palangka Raya, the adolescent age group, who often feel that they have good endurance, so they often ignore personal hygiene problems. Implementing this activity is an online extension through the zoom application, question-and-answer, and evaluation through posttest and pretest. The posttest and pretest results obtained were then performed statistical tests using the paired T-test. Based on the analysis results, there are significant differences in knowledge between before and after counseling. The average posttest score was 85.24, which was greater than the pretest average score, which was 79.92. Based on the paired T-test results, it is known that the p-value is 0.001 (p <0.05), so it can be concluded that there is a significant difference in knowledge between before and after counseling. As many as 80% of participants have a good level of knowledge.